Impacts of Social Media on University Students’ Academic Performance - Sharada Khanal; Pranjana Joshi (Journal of Balkumari College, 2025)
This paper presents impacts of social media on university students’ academic performance in public colleges of Chitwan. It aimed at examining the impact of social media on students’ performance and determining the co-relation between students’ revelations to social media and their academic performance. This study was quantitative in design. It was a cross-sectional survey based on self-administered 186 sets of questionnaire, incorporating demographic and five Likert scale questions through random sampling method covering bachelor and master level students of six public colleges of Chitwan district. The data were analyzed in frequency table and cross table using statistical tool like mean, standard deviation and co-relation. This study concluded that female respondents have greater revelations to social media networks. Further, age group of 18-22 have higher adeptness and familiarity with social media’s uses and applications. Students having greater revelations to social media networks for academic purposes, have good academic performance that was statistically significant (r = 0.347, P